1984
DOI: 10.1136/adc.59.1.18
|View full text |Cite
|
Sign up to set email alerts
|

New standards for neutral thermal environment of healthy very low birthweight infants in week one of life.

Abstract: SUMMARY It is generally accepted that low birthweight infants should be nursed at thermal neutral temperature-the environment in which oxygen consumption is at a minimum. Low birthweight infants do not, however, always show an increase in oxygen consumption at a temperature outside the neutral range, but react with a change in body temperature. We redefined therefore the neutral temperature for these infants as 'the ambient temperature at which the core temperature of the infant at rest is between 36&7 and 37 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(61 citation statements)
references
References 16 publications
1
55
1
4
Order By: Relevance
“…Incubator use for preterm infants has a long history. [5][6][7][8] Several studies have shown the effectiveness of incubator weaning at weights as low as 1500 g. [9][10][11] Glass et al's 12 article in 1968 may have set an earlier precedent for incubator weaning. A heterogeneous patient population in this small study showed increased growth at warmer incubator temperatures compared with a cooler environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incubator use for preterm infants has a long history. [5][6][7][8] Several studies have shown the effectiveness of incubator weaning at weights as low as 1500 g. [9][10][11] Glass et al's 12 article in 1968 may have set an earlier precedent for incubator weaning. A heterogeneous patient population in this small study showed increased growth at warmer incubator temperatures compared with a cooler environment.…”
Section: Discussionmentioning
confidence: 99%
“…Using an upper weight limit would have presented with the problem of potentially including SGA infants, who would be expected to wean to an open crib at a lower weight. A GA of 30 6 7 weeks was picked as an upper limit. GA is often estimated and choosing a more mature cohort presented with the possibility of including infants that were truly more mature, with corresponding larger birth weights.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Low birth weight infants are vulnerable to hypothermia (temperature r36.41C according to the previous definition by the AAP 6 ) since they have impaired ability to prevent heat loss 1 and decreased heat production capability. 7,8 The risk of cold stress is greatest at birth during the transition from the warm, wet, wellinsulated intrauterine environment to the cool, drafty delivery room. To reduce this risk, the Neonatal Resuscitation Program (NRP) has made the provision of warmth the first step in resuscitation of the newborn.…”
Section: Introductionmentioning
confidence: 99%
“…18 This interactive device ensures the maintenance of a thermal condition that takes account of each neonate's particular thermoregulatory requirements. Hence, the thermal environment fulfilled the criteria for thermoneutrality given by Sauer et al 19 For the second (mild warm condition) and third sessions (mild cool condition), T inc was set to T N + 2°C and T N -2°C, respectively. This experimental sequence was chosen in order to rule out a possible effect of thermal adaptation to cool exposure, since the latter can modify thermoregulatory responses and sleep structure.…”
Section: Experimental Designmentioning
confidence: 99%